2010
DOI: 10.1179/136217109x12577814486737
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fixed location variation in friction stir welding of steels with different carbon contents

Abstract: Dissimilar friction stir welding between steels with different carbon contents was carried out by placing the parent materials at two different fixed locations: the advancing side (AS) and the retreating side (RS). The phase transformation and the depth and width of the weld were affected by the fixed location. A smaller weld nugget was formed, and more martensite transformation occurred when the stronger SK5 steel was fixed at AS, compared to that at RS. This variation was attributed to the difference of temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…Changing the heating rate by 10 K/s (10°C/s) (i.e., slower or faster) in the analysis results in less than 15 K (15°C) variation from the average values. [64] This shows that although the temperature on the AS may rise to temperatures slightly higher than that of the RS due to firstly, the harder nature of the DSS, [63] and secondly the higher heat input resulted from the alignment of both rotational and translational movements of the probe in a same direction, [40][41][42][43][44] the temperature cannot still be far above the Ac 1 of the S275 steel (i.e., 1079 ± 24 K) during FSW, considering a fairly high thermal conductivity of steels.…”
Section: A Microstructure Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changing the heating rate by 10 K/s (10°C/s) (i.e., slower or faster) in the analysis results in less than 15 K (15°C) variation from the average values. [64] This shows that although the temperature on the AS may rise to temperatures slightly higher than that of the RS due to firstly, the harder nature of the DSS, [63] and secondly the higher heat input resulted from the alignment of both rotational and translational movements of the probe in a same direction, [40][41][42][43][44] the temperature cannot still be far above the Ac 1 of the S275 steel (i.e., 1079 ± 24 K) during FSW, considering a fairly high thermal conductivity of steels.…”
Section: A Microstructure Evolutionmentioning
confidence: 99%
“…The result of previous research on dissimilar FSW steels showed that placing the stronger steel on the AS increased the amount of martensite formation and reduced the size of SZ compared to a condition where the stronger steel is on the RS. [63] This was due to the higher temperature and stress resulting from placing the harder steel on the AS. High magnification OM of both materials in the weld region reveals variations in the microstructure and grain morphology in different zones (see Figures 4 and 5).…”
Section: A Microstructure Evolutionmentioning
confidence: 99%
“…Usually, the tool offset is considered in the softer material and it is better to place the softer material in the RS. 38,39,[42][43][44][45] According to previous efforts on the FSW of dissimilar metals, it has been demonstrated that when the softer material is placed at the AS, sound FSW (i.e. good quality in both surface morphology and microstructure) is achieved.…”
Section: Fsw Of Al-cu Bimetalsmentioning
confidence: 99%
“…It was discovered that the placement of the stronger material on the advancing side reduced the weld nugget size and increased the amount of martensite formation. The location of the strongest material on the advancing side led to higher temperature and stress due to the highest temperature on the advancing side [22]. It is evident from the literature that the FSW that involved materials that are mechanically apart involved mainly 2xxx as the weaker material.…”
Section: Introductionmentioning
confidence: 99%